1992
DOI: 10.1557/jmr.1992.1912
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical modification of polytetrafluoroethylene into oleophilic property using an ArF excimer laser

Abstract: Photochemical modification of the polytetrafluoroethylene (PTFE) with incorporation of the CH3 radical released from the B(CH3)3 molecule excited by an ArF excimer laser has been demonstrated. The incorporation of CH3 radicals and the depletion of fluorine atoms of the polymer surface were studied by XPS analysis and infrared ATR spectrum measurement. In these photochemical reactions, the photoirradiated surface changed into oleophilic. The properties were studied by contact angle measurement. The stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…With laser treatment in reactive atmosphere (e.g., hydrazine [100,101]) or under various liquids (e.g., B(CH 3 ) 3 [102,103]), the F--C bonds on the surface can be broken, CH 3 radicals or amino groups can be incorporated, allowing to apply a coating after laser treatment. This surface modification takes place without detectable ablation.…”
Section: Fluoropolymersmentioning
confidence: 99%
“…With laser treatment in reactive atmosphere (e.g., hydrazine [100,101]) or under various liquids (e.g., B(CH 3 ) 3 [102,103]), the F--C bonds on the surface can be broken, CH 3 radicals or amino groups can be incorporated, allowing to apply a coating after laser treatment. This surface modification takes place without detectable ablation.…”
Section: Fluoropolymersmentioning
confidence: 99%
“…4 On the other hand, our work has reported the laserinduced chemical modification of fluorocarbon-resin surface: the C-F bonds of the photoexcited surface are easily defluorinated by boron, aluminum, or hydrogen atoms, having a higher binding energy with fluorine atom than the C-F; dangling bonds of the defluorinated carbon atoms are bonded with a functional group. [5][6][7] This letter is based on these previous works. We concentrated on demonstrating that such defluorinated surface effects serve to form the chemical bonds of copper.…”
Section: Area-selective Nucleation Of Copper On Fluorocarbon-resin Sumentioning
confidence: 99%
“…A study of surface energy is found to be one of the best methods for estimating the nature of chemical change occurring on the polymer surfaces. The surface modification techniques such as irradiation with energetic ions [11], exposure to gaseous plasmas [12], UV radiation, etc [13][14][15] have been used for improving the surface properties of the polymeric materials without affecting the bulk properties [16]. In the present work, the irradiation effects of oxygen ions produced in the ECR plasma on the surfaces of the polyimide and the FEP have been studied.…”
Section: Introductionmentioning
confidence: 99%